AN AESTHETIC STUDY OF TRADITIONAL CULTURE IN NEZHA: BIRTH OF THE DEMON CHILD - Ngoi Guat Peng; Chen Zhen (Journal of Islamic, Social, Economics and Development, 2024)
Nezha: Birth of the Demon Child is an animated film that has attracted the attention of a large audience. Through its unique aesthetic features, the film successfully integrates excellent traditional Chinese culture into the context of modern cinema. This study conducted an in-depth aesthetic study on the traditional culture in the Chinese animated film "Nezha: Birth of the Demon Child". Through innovative character design, Chinese style scenes, costumes, music usage, and the construction of the "growth" theme, the film presented the absorption and integration of excellent traditional Chinese culture, and incorporated it into modern film narratives. It introduced a new perspective that integrates modern emotions and cultural heritage, successfully completing the revival and reshaping of traditional images and themes. This study emphasizes that this film has successfully participated in and promoted the discussion of traditional culture in the field of contemporary animation, marking a significant contribution to the global appreciation of Chinese cultural heritage. Through the examination of these elements, this study believes that "Nezha: Birth of the Demon Child" represents a critical period in Chinese animation. At this time, the integration of traditional themes with innovative storytelling and aesthetic practices can bring widespread cultural and commercial success, paving the way for future works seeking a balance between tradition and modernity. In order to delve deeper into the traditional cultural elements and their applications in the context of modern cinema in "Nezha: Birth of the Demon Child", this study first uses text analysis to systematically analyze the narrative structure and visual symbols in the film, in order to reveal its inherent cultural connotations and aesthetic characteristics. Secondly, using a comparative research method, this film will be compared with other animated works to highlight the uniqueness and innovation of "Nezha: Birth of the Demon Child" in traditional cultural expression.